The Effectiveness of Teaching Reading Descriptive Text Using Quiz Team Technique at SMPN 1 Tomilito - Gina Maulika Harun; Novriyanto Napu; Fahria Malabar (Transbahasa, 2025)
This study aims to determine the effectiveness of using the Quiz Team Technique in improving the descriptive text reading skills of seventh-grade students at SMP Negeri 1 Tomilito. The study used a quantitative approach with a one group pre-test post-test design. The research sample consisted of 20 students in class VII-A. The research instrument was a multiple-choice test that measured five reading indicators: determining the main idea, finding specific information, understanding vocabulary, analyzing text structure, and making inferences. The data were analyzed using a paired sample t-test with the help of SPSS. The results showed an increase in the average score of students from 45 on the pretest to 74.6 on the post-test. The hypothesis test results obtained a calculated t-value of 4.27 and a table t-value of 2.04 at a significance level of 0.05, so that the calculated t-value was greater than the table t-value. Thus, the alternative hypothesis was accepted and it can be concluded that the Quiz Team technique is effective in improving students' descriptive text reading skills. Improvements occurred in all reading indicators, especially in the ability to make inferences and find specific information. This technique has been proven to increase student activity, motivation, and cooperation during the learning process.